INTERNATIONAL OFFICIAL DOCUMENTS AS A SOURCE FOR IMPROVING INTERNAL QUALITY ASSURANCE AT MILITARY HIGHER EDUCATIONAL INSTITUTIONS - Kravets, Valentyna (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . In the current landscape marked by russia's armed aggression, Ukraine's higher military educational institutions continue to fortify their internal quality assurance systems. The enhancement of these systems is impossible without taking into account the best world practices and achievements in this area, notably gleaned from international official documents. This study aims to formulate proposals for improving internal quality assurance in military higher educational institutions of Ukraine, taking into account the provisions of international documents.M e t h o d s . The source base of the study is formed by documents of international organizations on quality assurance in the field of higher education, and international agreements of Ukraine on cooperation in the field of training military specialists. Dialectical, historical, comparative-legal methods are used to track the transformation of views on solving the problems of internal quality assurance in higher education institutions; systemstructural, formal-logical methods – to determine the provisions that should be taken into account in the process of improving internal quality assurance in military higher educational institutions of Ukraine; methods of analysis, generalization and synthesis – for the development of proposals.R e s u l t s . Summarized and systematized international official documents (agreements, protocols, conventions, recommendations, standards, declarations, communiqués, messages, charters) are classified into three categories: documents that define national policies to encourage higher education institutions to implement internal quality assurance systems; documents that provide methodological assistance in the formation of internal quality assurance systems; documents on cooperation in the field of training military specialists. The provisions that should be taken into account in the process of improving internal quality assurance in Ukraine's military higher educational institutions have been determined. Proposals for the implementation of these provisions in domestic regulations have been developed.C o n c l u s i o n s . This study's outcomes develop the ideas of other researchers on the expediency of taking into account the Standards and Recommendations for Quality Assurance in the European Higher Education Area, alongside NATO Quality Standards by Ukraine's military higher educational institutions in the process of improving internal quality assurance.
Keywords: internal quality assurance system, military higher educational institutions, international norms, normative acts, official documents